Current control of indexes of physical preparedness of students of different years of military establishment - Камаєв [Oleg Kamaev] Олег Іванович; Паєвський [Volodymyr Paievskyi] Володимир Валерійович; Шевченко [Oleg Shevchenko] Олег Олександрович (Slobozhanskyi Herald of Science and Sport, 2013)
Examined the dynamics of indices of physical training of cadets the on 1–4 courses. Presents the results of cadets for tightening on the lintel, pull the weight of 24 kg, running on 100, 400, 1000, 3000 m in the zone of obstacles. The got indexes of physical preparedness of students educed the reliable improvement of results from 1th on 4th years at p<0,05, except data of undercutting on a cross-bar (p>0,05), and allowed to define direction of increase of level of physical preparedness of students of military establishment.